Regularity and Rigidity for Nonlocal Curvatures in Conformal Geometry (Journal of Mathematical Study, 2020)
In this paper, we will explore the geometric effects of conformally covariantoperators and the induced nonlinear curvature equations in certain nonlocal nature.Mainly, we will prove some regularity and rigidity results for the distributional solutions to those equations.
Keywords: Regularity; spherical rigidity; nonlocal curvatures; conformal geometry.